Peran Kepemimpinan Kepala Sekolah Dalam Mengembangkan Kualitas Sumber Daya Manusia - Sekar Sabdo Wening; Hery Sawiji; Nur Rahmi Akbarini (Politeknik Kampar, 2023)
This study aims to find out: 1) the leadership role of the school headmaster in developing the quality of human resources at SMK Wikarya Karanganyar; 2) the strategic efforts made in developing the quality of human resources at SMK Wikarya Karanganyar; 3) what leadership styles are dominantly used by the headmaster of SMK Wikarya Karanganyar. This research is a qualitative research with a descriptive approach. The data sources of this research include primary and secondary data sources. The sampling technique was carried out by purposive sampling and snowball sampling. Data collection was carried out by observation, interviews, and document analysis. The validity test technique used is triangulation. Data analysis using interactive data analysis techniques. The results of this research analysis are as follows: 1) the leadership role of the school principal consists of several types, including educator, manager, supervisor, inovator, and motivator; 2) strategic efforts in developing the quality of human resources are carrying out various development activities routinely, optimizing the school climate, and always carry out supervision by the headmaster; 3) the dominant leadeship style applied by the headmaster at SMK Wikarya Karanganyar is democratic.